Photoswitchable dihetarylethene chemosensors for the selective 'naked-eye' detection of fluoride anions. Issue 46 (18th November 2015) - Dubonosov, Alexander D.; Bren, Vladimir A.; Minkin, Vladimir I.; Shepelenko, Evgenii N.; Tikhomirova, Karina S.; Starikov, Andrey G.; Revinskii, Yurii V.
Abstract: Novel photochromic thiazole-bridged dihetarylethenes with coumarinyl and thiophenyl substituents were synthesized. Their interaction either in ring-opened or in cyclic forms with fluoride, cyanide or acetate anions leads to drastic visibly detected changes in the electronic absorption spectra (yellow-to-violet color change), whereas other anions (Cl −, Br −, I −, SCN −, NO3 −, HSO4 − and H2 PO4 − ) do not induce any considerable colorimetric changes. Only in the case of fluoride ions, this effect is accompanied by very fast consecutive bleaching of solutions (violet-to-yellowish color change) owing to irreversible deprotonation of the NH moiety. This mechanism is supported by the results of the DFT calculations. Graphical abstract: